Employee–Organization Relationships and Team Performance: Role of Team Collective Efficacy - Li, Juexing; Jia, Liangding; Cai, Yahua; Kwan, Ho Kwong; You, Shuyang (Frontiers in Psychology, 2020)
Besides the previous social relationship perspective of employee–organization relationship (EOR) research, this study takes the social cognitive perspective to explore the role of team collective efficacy in mediating the relationship between EORs and team performance. This study further contends that team cohesion moderates the positive relationship between collective efficacy and team performance, thereby moderating the indirect relationship between EORs and team performance through collective efficacy. Data analyses of 231 teams in Study 1 and 63 teams in Study 2 support the hypotheses. Therefore, this study provides theoretical contributions to the EOR literature by introducing a new perspective at the team level and to the social cognitive literature by discussing a boundary condition of the effect of collective efficacy and team performance.